A study on purchasing behavior of UiTM students (male) Sabah branch on men's perfume / Yusrafie Hussein - Hussein, Yusrafie (2007)
The word perfume used today derives from the Latin "per fume", meaning through smoke. Perfumery, or the art of making perfumes, began in ancient Egypt but was developed and further refined by the Romans and the Arabs. Although perfume and perfumery also existed in East Asia, much of its fragrances are Incense based Knowledge of perfumery came to Europe as early as the 14th century due partially to Muslim influences and knowledge. During the Renaissance period, perfumes were used primarily by royalty and the wealthy to mask body odors resulting from the sanitary practices of the day. Partly due to this patronage, the western perfumery industry was created. By the 18th century, aromatic plants were being grown in the Grasse region of France to provide the growing perfume industry with raw materials. Even today, France remains the centre of the European perfume design and trade.